2020
DOI: 10.3389/fonc.2020.608815
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in the Pathogenesis and Treatment of Multiple Myeloma in the Context of the Bone Marrow Microenvironment

Abstract: Multiple myeloma (MM), the second most common hematological malignancy, is an incurable cancer of plasma cells. MM cells diffusely involves the bone marrow (BM) and establish a close interaction with the BM niche that in turn supports MM survival, proliferation, dissemination and drug resistance. In spite of remarkable progress in understanding MM biology and developing drugs targeting MM in the context of the BM niche, acquisition of multi-class drug resistance is almost universally inevitable. Exosomes are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
0
24
0
1
Order By: Relevance
“…More recently, also membrane-limited extracellular vesicles (EVs), both exosomes (Ø 50–150 nm) and microvesicles (Ø 150 nm–1 µm), which in MM are essentially produced by myeloma cells and MSCs, mediate the horizontal transfer of protein, lipids, and nucleic acids in their cargo, conveying information either locally or to cells at distant sites of the BM [ 22 , 23 ]. In fact, EVs have already been described to play roles in myeloma proliferation, development of osteolytic lesions, drug resistance, angiogenesis, and progression (see reviews [ 24 , 25 ]).…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, also membrane-limited extracellular vesicles (EVs), both exosomes (Ø 50–150 nm) and microvesicles (Ø 150 nm–1 µm), which in MM are essentially produced by myeloma cells and MSCs, mediate the horizontal transfer of protein, lipids, and nucleic acids in their cargo, conveying information either locally or to cells at distant sites of the BM [ 22 , 23 ]. In fact, EVs have already been described to play roles in myeloma proliferation, development of osteolytic lesions, drug resistance, angiogenesis, and progression (see reviews [ 24 , 25 ]).…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
“…Similarly, ncRNAs are also conveyed from MM-MSC-derived EVs into myeloma cells. The role of EVs targeting MSCs or derived from MM-MSCs in MM pathophysiology will be reviewed in the next section of this manuscript; for the roles of EVs on MSCs in MM, also see comprehensive reviews [ 24 , 58 ].…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
“…In addition to their immune-suppressive activity mediated by their secretion of IL-10 (an activator of Tregs and M2 macrophages), and TGF-β (an inhibitor of both cytotoxic T-cells and NK cells), M2 macrophages also promote MM cell proliferation, angiogenesis, and chemotherapy resistance [ 11 , 12 , 13 ] ( Figure 1 A). Nonclinical studies in animal models of MM have demonstrated that exosomes serve as regulators of the signaling networks within the BM microenvironment, activate anti-apoptotic mechanisms promoted by oncogenic proteins such as the signal transducer and activator of transcription 3 (STAT3), and cause immunosuppression by facilitating the growth of MDSCs [ 14 , 15 , 16 , 17 , 18 , 19 ]. Exosome-activated MDSCs have been implicated in development of other immunosuppressive cells, such as Tregs, tumor-promoting angiogenesis, proliferation of MM cells, and increased osteoclast activity contributing to the lytic bone lesions [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonclinical studies in animal models of MM have demonstrated that exosomes serve as regulators of the signaling networks within the BM microenvironment, activate anti-apoptotic mechanisms promoted by oncogenic proteins such as the signal transducer and activator of transcription 3 (STAT3), and cause immunosuppression by facilitating the growth of MDSCs [ 14 , 15 , 16 , 17 , 18 , 19 ]. Exosome-activated MDSCs have been implicated in development of other immunosuppressive cells, such as Tregs, tumor-promoting angiogenesis, proliferation of MM cells, and increased osteoclast activity contributing to the lytic bone lesions [ 14 , 15 , 16 , 17 , 18 , 19 ]. Complementing the immunosuppressive TME, T-cell exhaustion combined with high-level expression of immune-checkpoint ligands on MM cells are the main contributors to the immune evasion of MM cells [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Myeloma-derived exosomes are found to promote angiogenesis, osteolysis, plasma cell proliferation, and drug resistance ( 17 19 ). Furthermore, compounds that alter the production or the uptake of exosomes are under investigation in preclinical and clinical trials ( 20 ).…”
Section: Myeloma Cell Microenvironment and The Emerging Role Of Bone Marrow Adipocytesmentioning
confidence: 99%